Passive Bistatic Radar Detection Using Non-Stationary Transmitters of Opportunity - Ghazalli, Nasyitah (Cranfield University, 2017)
3MT presentation at the 2016 Defence and Security Doctoral Symposium.Passive Bistatic Radar (PBR) systems use non-cooperative illuminations of opportunity to detect, localise and track targets. They have attracted a lot of interest in recent years because 1) they can be operated and deployed at a relatively low cost 2) they are difficult to detect and hence allow covert operations in a hostile environment and 3) because of the proliferation of illuminators of opportunity.Various illuminators of opportunity from analogue signal sources to digital ones, have been studied and exploited in recent years, and these include commercial broadcast systems, cellular base stations and local area networks. The aim of this research is to investigate the potential of PBR target detection in the presence of non-random signals emitted by a moving transmitter of opportunity and without the use of a reference channel. Typical transmitters of opportunity could be, for example, satellites carrying a SAR system. This research will include a study of the waveform properties, an assessment of target tracking performance and a set of experimental trials to demonstrate the feasibility of the proposed solution.
Keywords: 'DSDS16 3MT'; 'DSDS16'; 'Passive radar'; 'Moving target'; 'Electrical and Electronic Engineering not elsewhere classified'